2018
DOI: 10.1088/2058-6272/aabc5c
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic acoustic modes in tokamak plasmas with anisotropic distribution and a radial equilibrium electric field

Abstract: Kinetic theory of geodesic acoustic modes in toroidal plasmas: a brief review Zhiyong QIU, Liu CHEN and Fulvio ZONCA -GAMs and ZFs in rotating large-aspectratio tokamak plasmas V I Ilgisonis, V P Lakhin, A I Smolyakov et al. - AbstractThe dispersion relation of standard geodesic acoustic modes in tokamak plasmas with anisotropic distribution and a radial equilibrium electric field is derived and analyzed. Both frequencies and damping rates increase with respect to the poloidal Mach number which indicates the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…In general, the MHD/CGL results [85,87,89] show the GAM frequency increasing with the χ (anisotropy) and λ ⊥ parameters. Similar behaviour was obtained from GK theory [86,90], and from an extended fluid model with Grad type evolution equations for the heat flux [89,91]. The effects of plasma anisotropy in combination with toroidal rotation have also been considered [88,92].…”
Section: Anisotropic Plasmas-gam and The Low Frequency (Zonal Flow) I...supporting
confidence: 63%
See 2 more Smart Citations
“…In general, the MHD/CGL results [85,87,89] show the GAM frequency increasing with the χ (anisotropy) and λ ⊥ parameters. Similar behaviour was obtained from GK theory [86,90], and from an extended fluid model with Grad type evolution equations for the heat flux [89,91]. The effects of plasma anisotropy in combination with toroidal rotation have also been considered [88,92].…”
Section: Anisotropic Plasmas-gam and The Low Frequency (Zonal Flow) I...supporting
confidence: 63%
“…With combined anisotropic pressure and an equilibrium radial electric field it was found that when p was larger than p ⊥ then E r had a stronger effect on the GAM frequency and damping [90]. But, overall, the pressure anisotropy effect on ω GAM and γ c.l.…”
Section: Damping and Amplitudementioning
confidence: 96%
See 1 more Smart Citation
“…2012; Gao 2013; Girardo et al. 2014; Ren 2015; Ming, Zhou & Wamg 2018; Conway, Smolyakov & Ido 2022) and numerically (see Biancalani et al. 2014; Novikau et al.…”
Section: Introductionmentioning
confidence: 98%
“…Geodesic acoustic modes have been largely studied in the literature, both analytically (see Garbet et al 2006;Smolyakov et al 2008;Zonca & Chen 2008;Qiu, Chen & Zonca 2009;Chakrabarti et al 2010;Zhang & Zhou 2010;Hassam & Kleva 2011;Zarzoso et al 2012;Gao 2013;Girardo et al 2014;Ren 2015;Ming, Zhou & Wamg 2018;Conway, Smolyakov & Ido 2022) and numerically (see Biancalani et al 2014;Novikau et al 2017;Grandgirard et al 2019). A key aspect in the linear gyro-kinetic theory of GAMs is the determination of mode frequency and damping rate.…”
Section: Introductionmentioning
confidence: 99%